2022
DOI: 10.4081/ijfs.2022.10220
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of <em>Helicobacter pylori</em> from raw chicken meat in Dhamar Governorate, Yemen

Abstract: Although Helicobacter pylori (H. pylori) is one of the most common bacterial pathogens of human, its natural reservoirs are still unclear. There is an increasing number of reports that document the occurrence of H. pylori in various foods. This study aimed at isolation of H. pylori from chicken meat sampled. Two hundred and sixty samples were collected randomly from slaughterhouses and markets in Dhamar Governorate, Yemen. Samples were enriched in Brain-Heart Infusion broth in microaerophilic conditions before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A closely related result was obtained by Khoder et al [ 43 ] who recorded 41% of healthy asymptomatic residents in the United Arab Emirates as H. pylori positive. While higher detection rates were observed in the Egyptian patients stools by Salem et al [ 7 ] and Shaaban et al [ 44 ] at 73.7% and 74.8%, respectively, using the rapid antigen test, On the other hand, lower results were reported by Hassan et al [ 45 ], Almashhadany and Mayass [ 46 ], and Seid et al [ 47 ] as 25, 30.4, and 18.45%, respectively. This disparity in H. pylori prevalence could be attributed to the sociodemographic status of the investigated population, geographical variations, and hygienic measures.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A closely related result was obtained by Khoder et al [ 43 ] who recorded 41% of healthy asymptomatic residents in the United Arab Emirates as H. pylori positive. While higher detection rates were observed in the Egyptian patients stools by Salem et al [ 7 ] and Shaaban et al [ 44 ] at 73.7% and 74.8%, respectively, using the rapid antigen test, On the other hand, lower results were reported by Hassan et al [ 45 ], Almashhadany and Mayass [ 46 ], and Seid et al [ 47 ] as 25, 30.4, and 18.45%, respectively. This disparity in H. pylori prevalence could be attributed to the sociodemographic status of the investigated population, geographical variations, and hygienic measures.…”
Section: Discussionmentioning
confidence: 87%
“…Based on molecular detection, males were more infected (25, 48.08%) compared with females (6, 16.67%). Contrarily, a slightly higher infection rate was detected in females (19.55%) than in males (16.44%) by using an antigen screening test [ 46 ]. Through molecular and serological studies, which were done by Castro et al [ 52 ], Mehesin et al [ 42 ], and Shaaban et al [ 44 ], there was no significant higher infection rate in females than males, as 14.6, 11.2 and 55.5, 44.5 and 79.7, 65.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…pylori (HP) is among the most widespread human bacterial pathogens worldwide [26]. Numerous variables affect the prevalence of H. pylori infection, including socioeconomic status, geographic location, living conditions, and personal hygiene [27]. The main reservoir of H. pylori is infected individuals; however, the majority of these infections are asymptomatic [28].…”
Section: Helicobacteriosismentioning
confidence: 99%
“…Many epidemiological studies have identified particularly drinking water sources as a major risk factor for H.pylori infection [24][25]. The second of the two hypotheses instead proposes that H.pylori is spread directly from person to person, typically within the family or close communities [26][27].…”
Section: Introductionmentioning
confidence: 99%